Demolding film
The release layer of a specific range was formed through the microslurry jet erosion test, which solved the problem of poor peeling of the release film after half-cutting and improved the yield rate.
Patent Information
- Application Number
- CN202380063716.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-06
- Filing Date
- 2023-08-29
- Publication Date
- 2025-04-18
AI Technical Summary
When manufacturing the sheet molded product, the release film cannot properly peel off the sheet molded product after half-cutting, resulting in a decrease in yield.
By forming a release layer with a erosion obtained by the microslurry jet erosion test to a specific range, the toughness of the release layer is improved.
When the sheet-shaped molded object is peeled off after half-cutting, the phenomenon of adhering to the half-cutting part is reduced and the yield rate is improved.
Smart Images

Figure BDA0005296512910000071 
Figure BDA0005296512910000081 
Figure BDA0005296512910000082
Abstract
Description
Technical Field
[0001] The present invention relates to a release film having a base film and a release layer, and relates to a release film useful as a film for various processes. Background Art
[0002] In the past, release films based on polyester films or the like had high heat resistance and mechanical properties and were used as process films for forming resin sheets such as adhesive sheets, cover films, ceramic slurries, and polymer electrolyte membranes. In addition, as release layers of release films, since they have good heat resistance and peelability, various release layers formed from coating compositions containing silicone have been proposed (e.g., Patent Documents 1 to 4).
[0003] Patent Documents 1 and 2 propose release films in which a release layer is formed using a coating composition containing polysiloxane having an unsaturated group, polysiloxane having a Si—H group, a platinum group metal catalyst, and an organic solvent.
[0004] In addition, as a technique suitable for coating in the stretching film formation of a substrate film (hereinafter referred to as "online coating"), a release film using an aqueous coating composition to form a release layer is proposed in Patent Document 3, wherein the aqueous coating composition contains an alkenyl-containing silicone and an Si-H-containing silicone. In addition, as an example, a release film using an alkenyl-containing silicone with a number average molecular weight of 25,000 and an Si-H-containing silicone with a number average molecular weight of 4,500 to form a release layer is disclosed.
[0005] Furthermore, Patent Document 4 proposes a release film which uses a film containing SiO 4 / 2 The present invention discloses a mold release film in which a mold release layer is formed by using an aqueous coating composition of an alkenyl-containing silicone having a Q unit and an Si-H-containing silicone. In addition, as an example, a mold release film is disclosed in which a mold release layer is formed by using an alkenyl-containing silicone having a Q unit and a number average molecular weight of 25,000 and an Si-H-containing silicone having a number average molecular weight of 4,500.
[0006] As described above, conventionally, when forming a release layer, a relatively high molecular weight polysiloxane containing an unsaturated group is generally used in order to facilitate formation of a helical structure of polydimethylsiloxane on the coating surface. This also applies to the case of using an organic solvent-based coating composition (e.g., Patent Documents 1 to 2).
[0007] On the other hand, there are also attempts to improve the releasability of a release film by measuring the hardness of the release layer of the release film and adjusting the hardness of the release layer. For example, in Patent Document 5, a release layer of a release film is separately prepared as a solid body and its rubber hardness is measured to try to evaluate the release properties of the release film. However, if this method is used, since the solid body of the release layer that has undergone a formation process different from the actual manufacturing process of the release film is evaluated, the release property evaluation is different from that of the actual release film.
[0008] In addition, as a technique for directly measuring the hardness of a release layer, Patent Document 6 proposes a release film for manufacturing ceramic green sheets, wherein the release film for manufacturing ceramic green sheets uses a polyester film as a substrate, has a release coating layer on one surface, and has a film elastic modulus of 2.0 GPa or more measured from the surface by a nanoindentation test on the release coating layer, and has a slippery coating layer containing particles on the other surface of the substrate. At this time, a nanoindentation test is performed using a microhardness evaluation device with a maximum indentation depth of 50 nm of the indenter to measure the film elastic modulus of the release coating layer.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2003-292894
[0012] Patent Document 2: Japanese Patent Application Publication No. 2003-292895
[0013] Patent Document 3: Japanese Patent No. 6077327
[0014] Patent Document 4: Japanese Patent Application Publication No. 2021-11081
[0015] Patent Document 5: Japanese Patent Application Publication No. 2012-6213
[0016] Patent Document 6: International Publication No. WO2019 / 065214 Summary of the invention
[0017] Problem that the invention aims to solve
[0018] However, when a release film is used to manufacture a sheet-like molded product, the sheet-like molded product such as a ceramic green sheet formed on the surface is often peeled off from the release film after being half-cut using a cutting blade and conveyed to the next process. In this case, even if the release film has sufficient peeling properties, the sheet-like molded product may not be properly peeled off at the starting point of peeling (half-cut portion), which leads to a decrease in yield.
[0019] The present inventors have studied the cause and found that during half-cutting, the sheet-like molded object is deformed by the cutting blade and adheres to the half-cut portion, resulting in partial improvement in the adhesion between the sheet-like molded object and the release film, making it difficult to peel off from the release film.
[0020] Furthermore, it was found that in order to avoid this phenomenon, it is not sufficient to simply increase the hardness of the release layer, and it is important to improve the toughness against microscopic physical effects.
[0021] Therefore, an object of the present invention is to provide a release film which is less likely to cause problems due to adhesion to the half-cut portion when peeling a sheet-like molded article after half-cutting.
[0022] Solutions for solving problems
[0023] The present inventors have conducted intensive studies to solve the above problems and have found that the above problems can be solved by forming a release layer having an erosion rate in a specific range as determined by a micropulp erosion test (MSE), thereby completing the present invention. That is, the present invention includes the following contents.
[0024] [1] A release film comprising a substrate film and a release layer, wherein the release layer has an erosion rate of 0.003 μm / g or more, wherein the erosion rate is a projected force of 0.019 μm / g for a polymethyl methacrylate resin in a microslurry jet erosion test to cause the average particle size (D 50 ) is the erosion rate of a slurry formed by dispersing 0.3 μm polygonal alumina particles in water.
[0025] [2] The release film according to [1], wherein the release layer is formed by reacting and solidifying a reaction-curable composition containing an organosilicon compound.
[0026] [3] The release film according to [2], wherein the reaction-curable composition comprises an alkenyl-containing organosilicon having a SiO 4 / 2 Represents the Q unit.
[0027] [4] The release film according to any one of [1] to [3], wherein the base film is a polyester film.
[0028] [5] The release film according to any one of [1] to [4], wherein the release film is a release film for a laminated ceramic capacitor or a release film for a resin sheet.
[0029] Effects of the Invention
[0030] According to the present invention, it is possible to provide a release film which is less likely to cause problems due to adhesion to a half-cut portion when peeling a sheet-like molded article after half-cutting.
[0031] The detailed reason for such an effect is not clear, but it is considered as follows. In the release layer with a certain degree of erosion obtained by the micro-pulp jet erosion test, the toughness to microscopic physical action is low (brittle), so when half-cutting is performed, the release layer is not denatured and becomes easy to break, and the sheet-like molded object closely attached to the release layer is deformed and effectively suppressed from adhering to the half-cut portion. This reason can also be understood from the following aspects: after the sheet-like molded object is peeled off, less sheet-like molded object remains in the half-cut portion of the release film. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a photograph showing an example in which the half-cutting property was evaluated as "○".
[0033] Figure 2 This is a photograph showing an example in which the half-cutting property evaluation was "△".
[0034] Figure 3 The photographs show examples in which the half-cutting property evaluation was "×". DETAILED DESCRIPTION
[0035] The release film of the present invention is a release film comprising a substrate film (hereinafter, sometimes referred to as "substrate") and a release layer, wherein the release layer has an erosion rate of 0.003 μm / g or more, wherein the erosion rate is a projecting force that projects an average particle size (D 50 ) is the erosion rate when a slurry is prepared by dispersing 0.3 μm polygonal alumina particles in water. First, the micropulp jet erosion test will be described.
[0036] [Microplasma jet erosion test]
[0037] The principle of this test is to measure the shape of the wear marks caused by the collision of particles, and to evaluate the hardness and softness of the material based on the degree of wear. By selecting particles and conditions, the toughness against microscopic physical effects can be evaluated. For the erosion rate of the MSE test, for example, a micro-particle jet erosion (MSE) tester, Palmeso Co., Ltd., device name MSE-A, is used to make particles collide with the measurement object, and the erosion depth is measured using a stylus shape measuring machine. The erosion rate is calculated from the erosion depth relative to the amount of particle collision.
[0038] As commonly used particles, resin, metal, ceramic and the like materials can be used and the average particle size is 10 μm or less. In order to make quantitative comparisons between measurement samples, polygonal alumina, spherical alumina, spherical silica and the like particles of a specific size can be used.
[0039] In the MSE test of the release layer in the present invention, the erosion rate is measured in the following manner. 50 ) 1 mass % slurry of polygonal alumina particles with a diameter of 0.3 mm Φ is projected onto the surface of the release layer from a nozzle with a diameter of 0.3 mm Φ and a distance of 4 mm from the nozzle tip to the sample to cut the release layer. The displacement to be cut relative to the slurry injection amount and the depth cut per 1 g of slurry are expressed as erosion rate (μm / g). That is, if the erosion rate value is large, it means that the material to be cut is brittle and weak, and if the erosion rate value is small, it means that the material to be cut is soft and strong.
[0040] The release layer in the present invention has an erosion rate in an MSE test of 0.003 μm / g or more, preferably 0.003 μm / g or more and 0.020 μm / g or less, and more preferably 0.004 μm / g or more and 0.010 μm / g or less.
[0041] If the erosion rate of the release layer is small, it is considered that the release layer is soft and strong. When the ceramic green sheet stacked on the surface of the release layer is half-cut, if the release layer is soft and strong, the ceramic green sheet cannot be cut neatly, but follows the release layer, so there is a possibility of elongation and residue of the ceramic green sheet in the half-cut portion. If the elongation and residue of the ceramic green sheet are generated in the half-cut portion, it cannot be evenly peeled off in the stripping process, so it is not preferred. In contrast, if the erosion rate is 0.003μm / g or more, the release layer is brittle when the ceramic green sheet is half-cut, so the cut portion can be cut instantly and completely. Therefore, no elongation or residue of the ceramic green sheet is generated, and it can be evenly peeled off in the stripping process, and it can be stably peeled off in the stripping process. In addition, if the erosion rate is below the upper limit of the above-mentioned preferred range, it is not easy for the release layer to detach or cohesive failure, so it is preferred.
[0042] As a method for adjusting the erosion rate, for example, a method for adjusting the density of crosslinking points of the resin contained in the release layer, specifically, by using an alkenyl-containing silicone or an Si-H-containing silicone with a lower number average molecular weight, or by using an Si-H-containing silicone with a high molar ratio of Si-H groups, the erosion rate can be increased. In addition, for example, a method for adjusting the density of the branched structure of the resin contained in the release layer, specifically, by using a SiO 4 / 2 The alkenyl-containing organosilicon of the Q unit shown above can increase the erosion rate.
[0043] In the above case, the erosion rate can be adjusted so as not to be too high by adjusting the molecular weight of the organosilicon containing alkenyl groups or the organosilicon containing Si-H groups, adjusting the molar ratio of the Q unit, or adjusting the molar ratio of the Si-H groups. In addition, the erosion rate can be reduced by adding a modifying resin that imparts flexibility to the release layer.
[0044] Furthermore, the erosion rate can be increased by using a resin with a high crosslinking density different from the mold release component, or by using a substance that increases the number of reactive sites, such as a low molecular weight crosslinking agent or coupling agent.
[0045] [Mold release layer]
[0046] As a release layer, as long as it contains a release agent component such as an organosilicon compound, a compound containing a long-chain alkyl group, a compound containing fluorine, an acrylic compound, etc., it can also contain an adhesive component, a crosslinking agent, a resin for modification, a solvent, a catalyst, a surfactant, a crosslinking reaction inhibitor, a coupling agent, etc. As a release layer, from the viewpoint of good heat resistance and stripping properties, and easy to appropriately control the surface free energy and erosion rate, it is preferably a release layer formed by reacting and solidifying a reaction-curable composition containing an organosilicon compound. In addition, from the viewpoint of considering the environment and safety, it is more preferably a release layer formed by reacting and solidifying an aqueous coating composition.
[0047] As the aqueous coating composition, it is preferred that the composition comprises an alkenyl-containing organosilicon and an Si—H-containing organosilicon, wherein the alkenyl-containing organosilicon has two or more alkenyl groups in the molecule and optionally has SiO 4 / 2 The Q unit shown in the figure has a number average molecular weight of 1000 or more and less than 10000, and the Si-H group-containing silicone has two or more Si-H groups in the molecule and a number average molecular weight of 1000 or more and 5000 or less. Each constituent component is described in detail below.
[0048] (Silicone containing olefin groups)
[0049] As the alkenyl group-containing organosilicon, there can be used organosilicon having two or more alkenyl groups in the molecule and having SiO 4 / 2 The alkenyl-containing organosilicon of the Q unit shown in the figure and / or the organosilicon having two or more alkenyl groups in the molecule but not having SiO 4 / 2 The Q unit shown is an alkenyl-containing organosilicon.
[0050] As the alkenyl group-containing organosilicon having a Q unit, any organosilicon having two or more alkenyl groups in the molecule and having SiO 4 / 2 The compound having a Q unit as shown and a siloxane bond in the main chain may be any compound, but preferably a polyorganosiloxane having an alkenyl group at the terminal and / or side chain. In addition, from the perspective of easy exfoliation and easy adjustment of the amount of alkenyl groups in one molecule, a copolymer containing a dialkylsiloxane unit or an alkylphenylsiloxane unit is preferred. The terminal silicon atom preferably has an alkenyl group, but may also be a trialkylsilane structure such as trimethylsilane.
[0051] As the alkenyl-containing organosilicon without Q unit, any compound may be used as long as it has two or more alkenyl groups in the molecule and a siloxane bond in the main chain, and preferably a polyorganosiloxane having alkenyl groups at the terminal and / or side chain. In addition, from the perspective of easy exfoliation and easy adjustment of the amount of alkenyl groups in one molecule, a copolymer containing a dialkylsiloxane unit or an alkylphenylsiloxane unit is preferred. The terminal silicon atom preferably has an alkenyl group, but may also be a trialkylsilane structure such as trimethylsilane.
[0052] In any organosilicon containing alkenyl groups, alkenyl groups may be introduced into any of a single terminal, both terminals, or a side chain, preferably at least into any terminal, more preferably into both terminals of the main chain. There are 2 or more alkenyl groups in the molecule, preferably 2 or more and 20 or less, more preferably 2 or more and 10 or less.
[0053] In the case of an alkenyl-containing organosilicon having a Q unit, as SiO 4 / 2 The content of the Q unit shown is preferably 0.5 mol% or more and 30 mol% or less, and more preferably 0.5 mol% or more and 20 mol% or less, when all silicon atoms including the terminal in the molecule are set to 100 mol%. If the content of the Q unit is 0.5 mol% or more, it is easy to form a dense release layer with high cohesive force, and it is easy to take into account the peelability and wettability of the release layer. If the content of the Q unit is 30 mol% or less, it is suppressed to form an excessively dense structure, and it is easy to suppress the brittleness of the coating film.
[0054] Examples of the alkenyl group-containing organosilicon include organopolysiloxane represented by the following general formula (I).
[0055]
[0056] (In the general formula (I), R 1 are optionally the same or different, and are alkenyl groups having 2 to 8 carbon atoms, or monovalent hydrocarbon groups having 1 to 16 carbon atoms including alkyl groups or aryl groups, and [SiO] b1 The silicon atom bonded R 1 At least one of them is an alkenyl group having 2 to 8 carbon atoms; R 2 are optionally the same or different, and are monovalent hydrocarbon groups having 1 to 16 carbon atoms, including alkyl groups or aryl groups; 1 They may be the same or different and are represented by the general formula (Ia).
[0057]
[0058] (In the general formula (Ia), R 1 R of the general formula (I) 1 The same, and R1 Optional: same or different. )
[0059] Including Y 1 In the general formula (I) as a whole, when all silicon atoms including the terminal are set to 100 mol%, a1 is 50 mol% or more and 98 mol% or less, b1 is 0 mol% or more and 10 mol% or less, c1 is 0 mol% or more and 30 mol% or less, and d1 is 0 mol% or more and 50 mol% or less. 1 In the general formula (I), R 1 Two or more of them are alkenyl groups having 2 or more and 8 or less carbon atoms.)
[0060] In the general formula (I), when c1 is 0 mol%, that is, in the case of an alkenyl group-containing organosilicon having no Q unit, examples of the alkenyl group-containing organosilicon include organopolysiloxanes represented by the following general formula (I′).
[0061]
[0062] With [SiO] a1 The silicon atom bonded R 2 It may be a monovalent hydrocarbon group including an alkyl group or an aryl group, and is preferably a monovalent hydrocarbon group having 1 to 16 carbon atoms selected from alkyl groups or aryl groups, more preferably a methyl group or a phenyl group, and still more preferably a methyl group.
[0063] With [SiO] b1 The silicon atom bonded R 1 It is an alkenyl group having 2 to 8 carbon atoms, or a monovalent hydrocarbon group containing an alkyl group or an aryl group, and at least one of them may be an alkenyl group having 2 to 8 carbon atoms, and preferably an alkenyl group having 2 to 8 carbon atoms, or a monovalent hydrocarbon group having 1 to 16 carbon atoms selected from an alkyl group or an aryl group. 1 When it is a hydrocarbon group other than an alkenyl group, a methyl group or a phenyl group is more preferred, and a methyl group is further preferred.
[0064] With [SiO] d1 The silicon atom bonded R 1 It may be an alkenyl group having 2 to 8 carbon atoms or a monovalent hydrocarbon group including an alkyl group or an aryl group, preferably an alkenyl group having 2 to 8 carbon atoms or a monovalent hydrocarbon group having 1 to 16 carbon atoms selected from an alkyl group or an aryl group, and more preferably a monovalent hydrocarbon group having 1 to 16 carbon atoms selected from an alkyl group or an aryl group. 1 When it is a hydrocarbon group other than an alkenyl group, a methyl group or a phenyl group is more preferred, and a methyl group is further preferred.
[0065] The two ends of the main chain are R 1Also bonded to [SiO] b1 The R on the silicon atom shown in 1 Similarly, as a preferred structure, an alkenyl group having 2 to 8 carbon atoms is particularly preferred because when the terminal alkenyl group reacts with the Si-H group, steric hindrance is small and the peeling property is easily improved.
[0066] In the general formula (Ia), R bonded to the terminal silicon atom 1 Also bonded to [SiO] b1 The R on the silicon atom shown in 1 Similarly, as a preferred structure, an alkenyl group having 2 to 8 carbon atoms is preferred because the cohesive force of the release layer is improved and the release property of the process material by an organic solvent is improved.
[0067] As R 1 Examples of the alkenyl group having 2 to 8 carbon atoms include vinyl, allyl, butenyl, pentenyl, and hexenyl. Among these, vinyl is particularly preferred.
[0068] Including Y 1 In the whole of the general formula (I), when all silicon atoms including the terminal are set to 100 mol%, a1 is 50 mol% or more and 98 mol% or less, preferably 70 mol% or more and 98 mol% or less. In addition, b1 is 0 mol% or more and 10 mol% or less, preferably 0 mol% or more and 5 mol% or less. c1 is 0.5 mol% or more and 30 mol% or less, preferably 0.5 mol% or more and 20 mol% or less. d1 is 0 mol% or more and 50 mol% or less, preferably 0 mol% or more and 30 mol% or less.
[0069] [SiO] a1 With [SiO] b1 When the total amount of the structural units of [SiO] is 100 mol%, from the viewpoint of localizing the hydrocarbon groups on the coating film surface in order to improve the peeling property, [SiO] a1 The content of the structural units is preferably in the range of 90 mol % to 100 mol %, and more preferably in the range of 95 mol % to 100 mol %.
[0070] The number average molecular weight of the alkenyl-containing silicone is preferably 1000 or more and less than 10000, more preferably 3000 or more and less than 10000. If the number average molecular weight is 1000 or more, the hydrocarbon group is easily localized on the surface of the coating film to obtain sufficient peeling properties. On the other hand, if the number average molecular weight is less than 10000, there is a tendency that the emulsification characteristics of the emulsified water-based coating composition become good and the uniform coating property also becomes good.
[0071] (Silicon containing Si-H group)
[0072] As the organosilicon containing Si-H groups, any compound can be used as long as it has two or more Si-H groups (i.e., two or more hydrogen atoms directly bonded to Si atoms) in the molecule and has a siloxane bond in the main chain, and polyorganosiloxane having Si-H groups in the side chain is preferred. In addition, from the perspective of easy exfoliation and easy adjustment of the amount of Si-H groups in one molecule, a copolymer containing a dialkylsiloxane unit or an alkylphenylsiloxane unit is preferred. The terminal silicon atom may have a Si-H group, and preferably a trialkylsilane structure such as trimethylsilane.
[0073] Examples of the Si-H group-containing organosilicon include organohydrogenpolysiloxane represented by the following general formula (II).
[0074]
[0075] (In general formula (II), R 3 They are optionally the same or different and are monovalent hydrocarbon groups having 1 to 16 carbon atoms, including alkyl or aryl groups. When a2+b2 is 100 mol%, a2 is 30 mol% to 90 mol%, and b2 is 10 mol% to 70 mol%.
[0076] As long as [SiO] a2 A hydrogen atom (hydrogen radical) is bonded to the silicon atom shown in 3 It may be a monovalent hydrocarbon group including an alkyl group or an aryl group, and is preferably a monovalent hydrocarbon group having 1 to 16 carbon atoms selected from alkyl groups or aryl groups.
[0077] With [SiO] b2 R bonded to the terminal Si atom 3 It may be a monovalent hydrocarbon group including an alkyl group or an aryl group, and is preferably a monovalent hydrocarbon group having 1 to 16 carbon atoms selected from alkyl groups or aryl groups.
[0078] About any R 3 , more preferably, the case where the number of carbon atoms of the alkyl or aryl group is smaller, the stereo hindrance is smaller, and the cross-linking reaction is easy to proceed. In addition, it is also preferred from the viewpoint of fluidity and uniformity of the reaction structure in the release layer. Therefore, as the alkyl group, methyl, ethyl, propyl, butyl, etc. are preferred, and as the aryl group, phenyl, tolyl, etc. are preferred.
[0079] If [SiO] a2 With [SiO] b2 The total amount of the structural units is 100 mol %, and as [SiO] a2The range of the structural unit is preferably 30 mol% or more and 90 mol% or less, and more preferably 40 mol% or more and 80 mol% or less. If [SiO] a2 The structural unit of [SiO] is 30 mol% or more, so that the crosslinking reaction sites become sufficient, the cohesive force of the release layer becomes large, and the scratch resistance and solvent resistance of the release layer are also good, so it is preferred. a2 The structural unit of is preferably 90 mol % or less because Si—H groups are less likely to remain in the release layer, the activity of the release layer surface is less likely to increase, and good releasability is maintained.
[0080] The number average molecular weight of the Si-H group-containing silicone in the present invention is preferably 1000 or more and 5000 or less, and more preferably 3000 or more and 5000 or less. If the number average molecular weight is 1000 or more, sufficient peeling properties are easily obtained. On the other hand, if the number average molecular weight is 5000 or less, there is a tendency that the emulsification characteristics of the emulsified aqueous coating composition become good and the coating uniformity also becomes good. In addition, the cross-linking reaction is easy to proceed effectively, the residual Si-H groups in the release layer decrease, and the peeling properties become good.
[0081] In the aqueous coating composition, relative to 100 parts by mass of the organosilicon containing alkenyl, it is preferred to include more than 1 part by mass and less than 50 parts by mass of the organosilicon containing Si-H groups, more preferably more than 2 parts by mass and less than 40 parts by mass, and further preferably more than 3 parts by mass and less than 30 parts by mass. If the content of the organosilicon containing Si-H groups is more than 1 part by mass, the crosslinking reaction sites become sufficient, and a dense crosslinking structure is easily formed, and the release layer property is improved, so it is preferred. If the content of the organosilicon containing Si-H groups reaches less than 50 parts by mass, the Si-H groups in the release layer are not easy to remain, the activity of the surface of the release layer is not easy to rise, and the stripping property is well maintained, so it is preferred.
[0082] (Polyvinyl alcohol resin)
[0083] When using a modifying resin, it is preferred to use a polyvinyl alcohol resin as a modifying resin for adjusting surface free energy, etc. As the polyvinyl alcohol resin, polyvinyl alcohol or its copolymer can be used. As the polyvinyl alcohol copolymer, examples include vinyl alcohol-vinyl acetate copolymers, vinyl alcohol-vinyl butyral copolymers, ethylene-vinyl alcohol copolymers, polyvinyl alcohol polymers having a silyl group in the molecule, etc., among which vinyl alcohol-vinyl acetate copolymers and ethylene-vinyl alcohol copolymers are preferred. In the case where the polyvinyl alcohol resin is a copolymer, the repeating unit derived from vinyl alcohol is preferably 70 mol% or more and 100 mol% or less, more preferably 85 mol% or more and 99 mol% or less.
[0084] The degree of polymerization of the polyvinyl alcohol-based resin in the present invention can be expressed by the viscosity of a 4% by mass aqueous solution at 20°C, and the viscosity is preferably 5 mPa·s or more and 50 mPa·s or less. If the viscosity is within the aforementioned numerical range, the miscibility in the aqueous coating composition is high, and a more uniform release layer is easily obtained. In other words, if the viscosity is 5 mPa·s or more, it is not easy to flow in the coating film after the release layer is formed, and it is not easy to reduce the release properties, so it is preferred. If the viscosity is 50 mPa·s or less, the viscosity of the aqueous coating composition as a whole is not easy to increase, and it is easy to apply uniformly, so it is preferred.
[0085] In addition, the polyvinyl alcohol-based resin may be mixed with the silicone before emulsification and may be used as an emulsifier.
[0086] Generally, polyvinyl alcohol is obtained by polymerizing vinyl acetate to form polyvinyl acetate, and then saponifying it, and the amount of saponification is expressed in the form of saponification degree. In the present invention, the saponification degree of the polyvinyl alcohol-based resin is preferably 85 mol% or more and 99 mol% or less. If the saponification degree is within the aforementioned numerical range, the miscibility in the aqueous coating composition is high, and a more uniform release layer is easily obtained. In particular, if the saponification degree is 85 mol% or more, the adhesion with the substrate is improved, and the miscibility with silicone is also good. If the saponification degree is 99% or less, the hydrophilicity of the release layer will not become too high, it is easy to maintain the cohesive force of the release layer coating, and it is not easy for the adhesion of the release layer to deteriorate.
[0087] As the polyvinyl alcohol-based resin, a commercially available product may be used as it is. Specific examples of the commercially available product include POVAL manufactured by Kuraray Co., Ltd. and GOHSENOL manufactured by Mitsubishi Chemical Corporation.
[0088] When a polyvinyl alcohol resin is used in the release layer, the release layer is used as a reference, and preferably contains more than 1% by mass and less than 20% by mass of the polyvinyl alcohol resin. As a more preferred range, it is more than 1% by mass and less than 15% by mass, and as a further preferred range, it is more than 1% by mass and less than 10% by mass. If the content of the polyvinyl alcohol resin is within the aforementioned numerical range, it is more suitable to take into account the two characteristics of miscibility with silicone and adhesion between the substrate and the release layer. In other words, if the content of the polyvinyl alcohol resin in the release layer is more than 1% by mass, the stability of the silicone emulsion in the coating liquid is easy to become good, and if it is less than 20% by mass, the release property is not easy to reduce.
[0089] (Platinum catalyst)
[0090] The cross-linking reaction between the alkenyl group-containing organosilicon and the Si—H group-containing organosilicon is an addition reaction, and in one embodiment, a platinum-based catalyst is preferably used to promote the reaction.
[0091] As the platinum-based catalyst, a known catalyst can be used, for example, platinum chloride and chloroplatinic acid. In consideration of dispersibility in silicone, the platinum-based catalyst can be 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum (0) complex (Karstedt catalyst), and uniform dispersibility can be ensured by dispersing it at the same time as emulsifying the silicone.
[0092] Regarding the content of the platinum-based catalyst, it is preferably contained in a range of 10 ppm or more and 400 ppm or less relative to the total mass of the organosilicon containing alkenyl groups and the organosilicon containing Si-H groups. By setting it to such a range, the curing of the organosilicon can be fully carried out, and the generation of organosilicon aggregates can be suppressed, and a release film with excellent surface properties can be obtained. If the mass ratio of the platinum element is below the upper limit, the addition reaction of the alkenyl group and the Si-H group becomes moderate, and there is a tendency to suppress the generation of organosilicon aggregates. From this viewpoint, the content of the platinum-based catalyst is more preferably less than 300 ppm, and more preferably less than 200 ppm. In addition, if the mass ratio of the platinum element is above the lower limit, the addition reaction is fully carried out, and it is difficult to cause poor curing of the organosilicon. From this viewpoint, the content of the platinum catalyst is more preferably more than 15 ppm, and more preferably more than 20 ppm.
[0093] (Water-based solvent)
[0094] When an aqueous coating composition is used, the aqueous coating composition generally contains an aqueous solvent in addition to the alkenyl-containing organosilicon and the Si-H-containing organosilicon. As the aqueous solvent, an aqueous solvent containing water is preferably used. In one embodiment, an aqueous dispersion of the alkenyl-containing organosilicon and an aqueous dispersion of the Si-H-containing organosilicon are used to prepare an aqueous coating composition. As the aqueous dispersion of each organosilicon, an aqueous emulsion is preferably used.
[0095] The release layer is formed from such an aqueous emulsion, and is formed by applying an aqueous coating composition containing the aqueous emulsion (hereinafter sometimes referred to as "aqueous coating liquid"). The aqueous coating liquid uses an aqueous solvent, and can form a release layer without using explosion-proof equipment and recovery equipment required for organic solvents in the film forming process. It may also contain some organic solvents as needed.
[0096] (Other ingredients)
[0097] When using an aqueous coating composition, in one embodiment, other additives such as surfactants, coupling agents, crosslinking reaction inhibitors, antistatic agents, ultraviolet absorbers, pigments, colorants, organic particles or inorganic particles, lubricants, anti-blocking agents, etc. can be mixed into the aqueous coating composition within a range that does not impair the effects of the invention.
[0098] (Surfactant)
[0099] In one embodiment, in order to promote wetting of the substrate film when the release layer is provided, a surfactant is preferably added to the aqueous coating composition. As the surfactant, anionic surfactants, cationic surfactants, nonionic surfactants, etc. can be listed, and one or more of them can also be used. In order to prevent the aggregation of various silicone aqueous emulsions and not affect the curing reaction of silicone, a nonionic surfactant is preferably used as an emulsifier.
[0100] As the nonionic surfactant, the HLB value is preferably in the range of 6 or more and 18 or less, and examples thereof include at least one selected from alkylene oxide adducts such as alkylene oxide adducts of higher alcohols and / or higher fatty acids, esters of alkylene oxide adducts of higher fatty acids and alcohols, alkylene oxide adducts of alkanolamides, alkylene oxide adducts of sorbitan esters, and alkylene oxide adducts of higher fatty acid glycerides. Here, the HLB value is a value calculated by Griffin's calculation formula.
[0101] As alkylene oxides, ethylene oxide, propylene oxide, and butylene oxide can be listed. One of these can be used, or multiple can be used. When multiple types are used, they can be block or random addition forms, but the HLB value is preferably in the range of 8 or more and 18 or less, and more preferably in the range of 10 or more and 15 or less. Among these nonionic surfactants, polyoxyethylene lauryl ether, polyoxyethylene tridecyl ether, etc. can be preferably listed. As needed, two or more nonionic surfactants can be mixed. If a nonionic surfactant whose HLB value deviates from this range is used as an emulsifier for an organosilicon aqueous dispersion, the emulsifying dispersion power and the stability of the aqueous dispersion are sometimes reduced.
[0102] The surfactant is preferably used in a range of 0.1% to 20% by mass relative to the total solid content, more preferably in a range of 0.2% to 15% by mass, and further preferably in a range of 0.5% to 10% by mass. If it is above the lower limit of the range, the emulsified state becomes good, and if it is below the upper limit of the range, it is not easy to cause re-peeling.
[0103] (Cross-linking Reaction Inhibitor)
[0104] In one embodiment, in order to suppress the activity of the platinum catalyst at room temperature in the state of the aqueous coating liquid, a reaction inhibitor is preferably contained. The reaction inhibitor is preferably a reaction inhibitor with an alkynyl group. As a reaction inhibitor with an alkynyl group, as long as there is an alkynyl group, there is no particular limitation, specifically, 1-ethynyl-1-cyclohexanol, 4-ethyl-1-octyne-3-ol, 3-methyl-1-dodecyne-3-ol, 3,7,11-trimethyl-1-dodecyne-3-ol, 1,1-diphenyl-2-propyne-3-ol, 3-ethyl-6-ethyl-1-nonyne-3-ol, 3-methyl-1-pentadecane-3-ol, 2,5-dimethyl-3-hexyne-2,5-diol, 3-phenyl-1-butyne-3-ol can be exemplified. In the present invention, since it is an aqueous coating liquid, it is preferred to use the reaction inhibitor with an alkynyl group and a hydroxyl group illustrated from the balance of affinity solubility in water and coordination ability for platinum and boiling point. Alternatively, the platinum-based catalyst may be mixed with a general organopolysiloxane to be added to the aqueous coating liquid and used in the form of an aqueous emulsion.
[0105] The content of the crosslinking reaction inhibitor is preferably 5 ppm or more and 1000 ppm or less relative to the mass of the aqueous coating composition for forming the release layer, more preferably 10 ppm or more and 700 ppm or less, and further preferably 20 ppm or more and 500 ppm or less. When the content of the crosslinking reaction inhibitor is above the lower limit, there is a tendency that the storage period becomes longer, the addition curing reaction of the silicone is difficult to proceed at room temperature, and silicone aggregates are not easily generated. In addition, if the content of the crosslinking reaction inhibitor is below the upper limit, after the object material is peeled off, the silicone is not easily transferred to the object material, and the amount of the reaction inhibitor volatilized during the heat treatment is reduced, so it is not easy to cause contamination inside the oven.
[0106] (Coupling agent)
[0107] In one embodiment, a coupling agent may be added to the aqueous coating composition to improve the adhesion between the organosilicon component and the substrate film. The coupling agent may be, for example, a compound represented by the general formula YRSiX3, for example, a silane coupling agent. Here, Y is an organic functional group such as a vinyl group, an epoxy group, an amino group, a thiol group, etc., and Y is particularly preferably an epoxy group or a vinyl group.
[0108] R is an alkylene group such as methylene, ethylene, or propylene, or a single bond. X is a hydrolyzable group such as methoxy, ethoxy, or acetoxy, or an alkyl group, and at least one of the three Xs is a hydrolyzable group, and preferably all three Xs are hydrolyzable groups. As the hydrolyzable group, a methoxy group is preferred.
[0109] Preferred silane coupling agents include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, vinyltrimethoxysilane, vinyltri(2-methoxyethoxy)silane, and vinylmethyldimethoxysilane.
[0110] Other examples of coupling agents include organometallic compounds containing metals such as zirconium, titanium, and aluminum. The organometallic compounds are preferably classified as alkoxides, chelates, and acylates. Specific examples include zirconium tetraacetylacetonate, zirconium acetate, titanium acetylacetonate, triethanolamine titanate, and titanium lactate, but are not limited to these.
[0111] Furthermore, as the coupling agent, two or more coupling agents may be used in combination, such as a silane coupling agent in which Y is an epoxy group and a silane coupling agent in which Y is a vinyl group.
[0112] In one embodiment, by adding a coupling agent, the durable adhesion between silicone as the main component of the release layer and polyester film is improved. For example, when casting a resin sheet by a solution casting method using an organic solvent, the organic solvent component sometimes penetrates into the release layer, and the release layer may be corroded, but the corrosion can be suppressed by adding a coupling agent. When casting a resin sheet by a melt casting method at high temperature, the release layer is exposed to high temperature and may be thermally degraded, but by adding a coupling agent, thermal degradation can be suppressed and the release layer can be maintained.
[0113] From the above viewpoints, the content of the coupling agent is preferably 0.1 parts by mass or more and 20 parts by mass or less, and more preferably 1 part by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the total of the alkenyl group-containing silicone and the Si—H group-containing silicone contained in the release layer.
[0114] (Preparation of Silicone Aqueous Dispersion)
[0115] When an aqueous coating composition is used, in one embodiment, the preparation of an aqueous emulsion can be listed as a method of using a predetermined alkenyl-containing silicone or Si-H-containing silicone, an aqueous solvent and a surfactant and emulsifying them. These components can be emulsified using a known method, and the following method can be listed, for example, a method of mechanically emulsifying a predetermined silicone, a surfactant and other components as required in an aqueous medium using a stirring device such as a homogenizer, a vacuum emulsifier (AGIHOMO MIXER), and a super planetary stirrer.
[0116] In addition, the particle size of the aqueous dispersion can be adjusted by adjusting the size of the stirring blade, the stirring speed and the stirring time. The average particle size of the dispersed particles of each silicone aqueous dispersion is preferably 200 nm or less, more preferably 100 nm or more and 200 nm or less.
[0117] [Base film]
[0118] The substrate film in the present invention is not particularly limited, and examples thereof include sheets or films formed of polyesters such as polyethylene terephthalate and polyethylene naphthalate, polyolefins such as polycarbonate, polyethylene and polypropylene, polystyrene triacetate, acrylics, polyimides, etc. Among them, films formed of polyesters are preferred from the viewpoint of excellent mechanical properties and heat resistance and a good balance between these properties and price. Hereinafter, the case of a polyester film will be described as an example, but in the case of using other resin films, the copolymer components, blending components, additives, film preparation methods, laminated structures, etc. are the same as follows.
[0119] (Polyester film)
[0120] The polyester constituting the polyester film used as a substrate film is not particularly limited, and a polyester generally used as a substrate for a release film can be used to form a film. Preferably, it is a crystalline linear saturated polyester formed by an aromatic dibasic acid component and a diol component, and more preferably, for example, polyethylene terephthalate, polyethylene 2,6-naphthalate, polybutylene terephthalate, poly(1,3-propylene terephthalate), or a copolymer with the constituent components of these resins as the main component. In particular, it is particularly suitable for a polyester film formed by polyethylene terephthalate. In polyethylene terephthalate, the repeating unit of ethylene terephthalate is preferably 90 mol% or more, more preferably 95 mol% or more, and other dicarboxylic acid components and diol components may also be copolymerized in small amounts. For example, from the viewpoint of cost, it is preferably manufactured only from terephthalic acid and ethylene glycol. Furthermore, known additives such as antioxidants, light stabilizers, ultraviolet absorbers, crystallizing agents, etc. may be added within the range not impairing the effects of the release film of the present invention. The polyester film is preferably a biaxially oriented polyester film because of its high elastic modulus in both directions.
[0121] The intrinsic viscosity of the polyester film is preferably 0.50 dl / g or more and 0.70 dl / g or less, and more preferably 0.52 dl / g or more and 0.62 dl / g or less. When the intrinsic viscosity is 0.50 dl / g or more, a large amount of breakage will not occur during the stretching process, so it is preferred. On the contrary, when it is 0.70 dl / g or less, the cutting property when cutting into a prescribed product width is good, and dimensional defects will not occur, so it is preferred. In addition, the raw material pellets are preferably fully vacuum dried.
[0122] In addition, when it is simply referred to as "polyester film" in this specification, it means a polyester film which has a surface layer A and a surface layer B (laminated).
[0123] The method for producing the polyester film of the present invention is not particularly limited, and a conventionally commonly used method can be used. For example, the polyester can be melted and extruded into a film in an extruder, and cooled with a rotating cooling drum to obtain an unstretched film, and the unstretched film can be biaxially stretched to obtain the film. The biaxially stretched film can be obtained by a method in which a uniaxially stretched film in the longitudinal or transverse direction is biaxially stretched successively in the transverse direction or longitudinal direction, or by a method in which an unstretched film is biaxially stretched simultaneously in the longitudinal and transverse directions.
[0124] In the present invention, the stretching temperature during stretching of the polyester film is preferably set to be equal to or higher than the secondary transition point (Tg) of the polyester. The film is preferably stretched 1 to 8 times in each of the longitudinal and transverse directions, and particularly preferably stretched 2 to 6 times.
[0125] The thickness of the polyester film is preferably 12 μm or more and 50 μm or less, more preferably 15 μm or more and 38 μm or less, and even more preferably 19 μm or more and 33 μm or less. If the thickness of the film is 12 μm or more, there is no need to worry about deformation due to heat during film production, processing, and molding, so it is preferred. On the other hand, if the thickness of the film is 50 μm or less, the amount of film discarded after use will not become extremely large, which is preferred in terms of reducing the environmental burden.
[0126] The polyester film substrate may be a single layer or a multilayer of two or more layers. For example, the substrate film may be a polyester film having a surface layer A substantially free of particles having a particle size of 1.0 μm or more and a surface layer B containing particles. The surface layer A preferably substantially does not contain inorganic particles having a particle size of 1.0 μm or more.
[0127] In this embodiment, particles having a particle size of less than 1.0 μm and 1 nm or more may exist in the surface layer A. By making the surface layer A substantially free of particles having a particle size of 1.0 μm or more, such as inorganic particles, it is possible to reduce the phenomenon that the particle shape in the substrate is transferred to the resin sheet and causes problems.
[0128] In one embodiment, by making the surface layer A also contain no particles having a particle diameter of less than 1.0 μm, it is possible to more effectively suppress the phenomenon in which the particle shape in the substrate is transferred to the resin sheet and causes a problem.
[0129] In one embodiment, the polyester film substrate is preferably a laminated film having a surface layer A substantially free of inorganic particles on at least one surface. This can more effectively prevent the particle shape in the substrate from being transferred to the resin sheet and causing problems.
[0130] For example, it is preferable that the surface layer A substantially does not contain particles having a particle size of less than 1.0 μm and also substantially does not contain particles having a particle size of 1.0 μm or more.
[0131] Here, in the present invention, "substantially free of particles" means that, for example, in the case of inorganic particles smaller than 1.0 μm, when the inorganic elements are quantified by fluorescent X-ray analysis, the content is 50 ppm or less, preferably 10 ppm or less, and most preferably below the detection limit. This is because, even if particles are not actively added to the film, sometimes contamination components from foreign matter, dirt attached to the production line or equipment in the raw resin or film manufacturing process will peel off and mix into the film. In addition, "substantially free of particles with a particle size of 1.0 μm or more" means that particles with a particle size of 1.0 μm or more are not actively included.
[0132] In the case of a laminated polyester film having a multilayer structure of two or more layers, it is preferred that a surface layer B containing inorganic particles and the like is provided on the opposite side of a surface layer A containing substantially no inorganic particles.
[0133] As a stacked structure, if the layer on one side of the coating release layer is set to the A layer, the layer on its opposite side is set to the B layer, and the core layer other than them is set to the C layer, the layer structure in the thickness direction can list the stacked structures such as release layer / A / B or release layer / A / C / B. Of course, the C layer can also be a plurality of layers. In addition, the surface layer B also can not contain inorganic particles. In this case, in order to give the slipperiness for winding the film into a roll, it is preferred that a coating layer at least comprising inorganic particles and a binder is provided on the surface layer B.
[0134] In the polyester film substrate of the present invention, from the viewpoint of the slipperiness of the film and the ease of air discharge, the surface layer B forming the surface opposite to the coating release layer preferably contains inorganic particles, and silicon dioxide particles and / or calcium carbonate particles are particularly preferably used. The content of the inorganic particles contained in the surface layer B is preferably 1000 ppm or more and 15000 ppm or less based on the total amount of the inorganic particles.
[0135] At this time, the regional surface average roughness (Sa) of the film of surface layer B is preferably in the range of more than 1nm and less than 40nm. More preferably, it is in the range of more than 5nm and less than 35nm. When the total of silicon dioxide particles and / or calcium carbonate particles is more than 1000ppm and Sa is more than 1nm, when the film is rolled into a roll, air can be uniformly dispersed, and the winding state is good and the planarity is good, therefore, it is suitable for manufacturing ultra-thin layer ceramic green sheets. In addition, when the total of silicon dioxide particles and / or calcium carbonate particles is less than 15000ppm and Sa is less than 40nm, it is not easy to gather lubricants, and coarse protrusions will not be formed. Therefore, when manufacturing ultra-thin layer ceramic green sheets, the quality is stable, so it is preferred.
[0136] As the particles contained in the above-mentioned B layer, in addition to using silicon dioxide and / or calcium carbonate, inactive inorganic particles and / or heat-resistant organic particles, etc. can also be used. From the viewpoint of transparency and cost, silicon dioxide particles and / or calcium carbonate particles are more preferably used. In addition, as other inorganic particles that can be used, aluminum oxide-silicon dioxide composite oxide particles, hydroxyapatite particles, etc. can be listed. In addition, as heat-resistant organic particles, cross-linked polyacrylic acid particles, cross-linked polystyrene particles, benzoguanamine particles, etc. can be listed. In addition, when using silicon dioxide particles, porous colloidal silica is preferred, and when using calcium carbonate particles, from the viewpoint of preventing the lubricant from falling off, it is preferred to utilize polyacrylic acid polymer compounds to implement surface-treated light calcium carbonate.
[0137] The average particle size of the inorganic particles added to the surface layer B is preferably 0.1 μm or more and 2.0 μm or less, and particularly preferably 0.5 μm or more and 1.0 μm or less. If the average particle size of the inorganic particles is 0.1 μm or more, the slip property of the release film is good, so it is preferred. In addition, if the average particle size is 2.0 μm or less, there is no concern about adverse effects on the smoothness of the release layer surface, and therefore, there is no concern about pinholes in the ceramic green sheet, so it is preferred.
[0138] From the viewpoint of reducing pinholes and preventing the incorporation of inorganic particles such as a lubricant, it is preferred that no recycled raw materials or the like be used in the surface layer A as a layer on the side where the release layer is provided.
[0139] The thickness ratio of the surface layer A as a layer on the side of the release layer is preferably 20% or more and 50% or less of the thickness of all layers of the base film. If it is 20% or more, it is not easy to be affected by particles contained in the surface layer B and the like from the inside of the film, and the regional surface average roughness Sa easily meets the above range, so it is preferred. If it is less than 50% of the thickness of all layers of the base film, the use ratio of recycled raw materials in the surface layer B can be increased, and the environmental burden is small, so it is preferred.
[0140] In addition, from the viewpoint of economic efficiency, 50% by mass or more and 90% by mass or less of recycled raw materials of film scraps or plastic bottles may be used in the layer other than the surface layer A (surface layer B or the intermediate layer C). In this case, the type, amount, particle size and regional surface average roughness (Sa) of the lubricant contained in the B layer preferably also meet the above ranges.
[0141] In addition, in order to improve the adhesion of a release layer to be applied later or to prevent static electricity, a coating layer may be provided on the surface of the surface layer A and / or surface layer B of the film before stretching or after uniaxial stretching in the film forming process, or a surface treatment may be performed.
[0142] In one embodiment, in order to improve the adhesion with the release layer, the release layer forming surface coated with the aqueous coating composition can be surface treated or an easy-adhesion layer can be provided. As surface treatment, plasma treatment, corona discharge treatment, ultraviolet treatment, flame treatment and electron beam / radiation treatment can be listed, and as an easy-adhesion layer, a layer containing the same resin as the substrate film, and then containing an antistatic agent, a pigment, a surfactant, a lubricant, an anti-blocking agent, etc. can be listed. When a coupling agent or the like is added to the aqueous coating composition, even if an easy-adhesion layer is not provided, the release layer can also have sufficient adhesion to the substrate film.
[0143] [Formation of Release Layer]
[0144] In one embodiment, the release layer is formed by applying an aqueous coating composition comprising an aqueous emulsion of an alkenyl-containing organosilicon and an aqueous emulsion of an Si-H-containing organosilicon. In this case, the release layer is formed on at least one surface of the substrate film. The release layer is formed by applying the aqueous coating liquid on the substrate film, and then heating / drying the aqueous coating liquid to react and solidify the components of the aqueous coating liquid to form the release layer. The release layer is preferably formed in the film forming process.
[0145] The thickness of the release layer is preferably 5 nm or more and 100 nm or less in terms of thickness after drying. If the thickness of the release layer is above the lower limit, it is easy to obtain sufficient peelability. If it is below the upper limit, there is a tendency that the peel strength is not easy to increase. In addition, there is a tendency that the release layer component of the water-based coating liquid has a high concentration and does not need to increase the coating amount, making it easy to apply. Therefore, the thickness of the release layer is more preferably 5 nm or more and 70 nm or less, and more preferably 5 nm or more and 50 nm or less.
[0146] When the water-based coating liquid is applied to the substrate film, the solid content concentration is preferably 20% by mass or less, more preferably 1% by mass or more and 10% by mass or less, based on the release layer component in the water-based coating liquid. If the solid content concentration of the release layer component in the water-based coating liquid is above the lower limit, there is a tendency that the film-forming property becomes good. In addition, if the solid content concentration is below the upper limit, the stability of the water-based coating liquid and the appearance of the release layer tend to become good. As an aqueous solvent for adjusting the solid content concentration, water is preferably used.
[0147] The aqueous coating liquid applied to the substrate film to form the release layer can be applied at any stage, but is preferably applied during the production process of the polyester film, and more preferably applied to the polyester film before the orientation crystallization is completed. Thereafter, after stretching in at least one direction, heat treatment can be performed to complete the crystal orientation.
[0148] Here, the polyester film before the completion of crystal orientation includes: an unstretched film; a uniaxially oriented film obtained by orienting the unstretched film along either the longitudinal direction (hereinafter sometimes referred to as the film continuous film forming direction, the length direction, or the MD direction) or the transverse direction (hereinafter sometimes referred to as the direction orthogonal to the longitudinal direction, the width direction, or the TD direction); a film obtained by further stretching and orienting the unstretched film at a low ratio along both the longitudinal and transverse directions (a biaxially stretched film before the orientation crystallization is finally completed by re-stretching along the longitudinal or transverse direction), etc.
[0149] Among them, it is preferred that a water-based coating liquid is applied to an unstretched film or a uniaxially stretched film obtained by orientation in one direction, and the so-called online coating is directly performed by longitudinal stretching and / or transverse stretching and heat fixing. The release layer can be dried by a stretching process or a heat fixing treatment after coating, and a drying process can be added as needed. In addition, when a catalyst is used to cure the composition to obtain a cured film, it can be cured by a stretching process or a heat fixing treatment, and a curing process can be further added as needed.
[0150] When applying the water-based coating liquid to the polyester film, it is preferred that: as a pretreatment for improving the coating properties, the film surface is subjected to a physical treatment such as corona surface treatment, flame treatment, plasma treatment, etc.; or, the aforementioned emulsifier is combined with the composition as a wetting agent, and a surfactant is additionally added as a wetting agent.
[0151] As the coating method, any known coating method can be applied, and for example, roll coating, gravure coating, roll brush coating, spray coating, air knife coating, impregnation, curtain coating, etc. can be used alone or in combination.
[0152] [Properties of release film]
[0153] In the present invention, the surface free energy of the release layer in the test method described later is preferably in the range of 10mN / m or more and 40mN / m or less, more preferably in the range of 12mN / m or more and 38mN / m or less, further preferably in the range of 14mN / m or more and 36mN / m or less, and particularly preferably in the range of 15mN / m or more and 35mN / m or more. If the surface free energy of the release layer is below the upper limit, the adhesion is reduced and it is not easy to be re-stripped. In addition, if it is above the lower limit, it is not easy to produce defects caused by the repulsion of the processing layer such as the ceramic sheet and the resin sheet coated on the surface of the release layer, and it is not easy to produce pinhole defects.
[0154] [use]
[0155] The release film of the present invention can be used as a process film used in manufacturing a laminated ceramic capacitor, casting a resin sheet, etc. In particular, even if a thin film resin sheet having a thickness of 1 μm or less after drying is produced, the wettability is good, so that pinholes in the processing layer are reduced. For example, when used as a release film for green sheet production, the defect rate of thin-walled laminated ceramic capacitors can be reduced.
[0156] Example
[0157] The present invention will be described in more detail below with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples. The evaluation methods of physical properties and the like in the following Examples are as follows.
[0158] (1) Coating uniformity of release layer
[0159] The release film was cut into A4 sheets, and the release layer was visually observed using a fluorescent lamp or a halogen lamp. The number of aggregated coating defects (number per A4 sheet) was compared and evaluated based on the following criteria.
[0160] ◎: No coating defects
[0161] ○: 1 to 2 coating defects
[0162] △: 3 to 5 coating defects
[0163] ×: There are 6 or more coating defects
[0164] (2) Surface free energy of release layer
[0165] For samples humidified at 23°C and 50% RH for 24 hours, a contact angle meter (DMo-501 manufactured by Kyowa Interface Science Co., Ltd.) was used to measure the static contact angle when water was added and allowed to stand for 30 seconds. The static contact angles of ethylene glycol and diiodomethane were measured in the same manner, and the surface tension components of the following liquids were used to establish the following simultaneous equations related to the surface tension components of the release layer (the respective measurement liquids of water, ethylene glycol, and diiodomethane were set as 1, 2, and 3, γLD represents the dispersion force component of the liquid, γLP represents the polar force component of the liquid, γLH represents the hydrogen bonding component of the liquid, and γL represents the total value of the surface tension components in the liquid. In addition, γSD represents the dispersion force component of the release layer, γSP represents the polar force component of the release layer, and γSH represents the hydrogen bonding component of the release layer. In addition, θ represents the contact angle.).
[0166] (γSD·γLD1) 1 / 2 +(γSP·γLP1) 1 / 2 +(γSH·γLH1) 1 / 2 =γL1(1+cosθ1) / 2
[0167] (γSD·γLD2) 1 / 2 +(γSP·γLP2) 1 / 2 +(γSH·γLH2) 1 / 2 =γL2(1+cosθ2) / 2
[0168] (γSD·γLD3) 1 / 2 +(γSP·γLP3) 1 / 2 +(γSH·γLH3) 1 / 2 =γL3(1+cosθ3) / 2
[0169] It should be noted that γLD, γLP, γLH, and γL of water, ethylene glycol, and diiodomethane are as shown in Table 1.
[0170] [Table 1]
[0171]
[0172] Next, the surface free energy γS of the release layer surface is calculated using the following formula from the numerical values of γSD, γSP, and γSH obtained as described above.
[0173] γS=γSD+γSP+γSH
[0174] (3) Erosion rate
[0175] The average particle size (D 50) 0.3 μm polygonal alumina particles (MicroPolishAlumina manufactured by BUEHLER) were dispersed in water to prepare a slurry containing 1 mass % of the polygonal alumina particles relative to the total mass of the slurry. A micro slurry jet erosion (MSE) tester (manufactured by Palmeso Co., Ltd., device name MSE-A) was used to fix the release film on the sample stage. The projection distance of the nozzle used to spray the slurry was set to 4 mm.
[0176] The diameter of the nozzle for projecting (spraying) particles was set to 0.3 mm Φ, and the particles collided with the surface of the release layer to cut the release layer. For the spraying intensity at this time, polymethyl methacrylate resin (KURARAY CO., LTD., PARAGLAS P, sheet thickness 2 mm) was cut in advance under the same experimental conditions, and the standard projection force was calculated from the displacement of the cut relative to the slurry injection amount (i.e., the cutting depth when 1 g of slurry was blown), and the standard projection force was determined based on this value. When using the average particle size (D 50 In this embodiment of the invention, the projection force when cutting 0.019 μm / g of polymethyl methacrylate resin is set as the standard projection force. The erosion depth of the release layer is measured with this standard projection force. In the above-mentioned testing machine, since the projection force is adjusted by the projection air pressure, if the projection force is determined, the projection air pressure and the projection air volume are also determined.
[0177] The erosion depth was measured using a stylus-type surface shape measuring machine (manufactured by Kosaka Laboratory Co., Ltd., model PU-EU1, needle tip R: 0.5μm, load: 50μN, measurement magnification: 50,000, measurement length: 4mm, measurement speed: 0.1mm / s). In more detail, first, the unworn end reference areas A and B in the measurement length are used to perform tilt correction. Next, the height difference from the regression line serving as the reference to the center C of the wear mark (average value of 50μm width) is measured. Next, the height difference data under 0g projection (untreated surface) and the height difference data under each projection amount are obtained to obtain the erosion depth. From the obtained projection amount-erosion depth data, the erosion rate (μm / g) is determined by the change in erosion depth between 0g and 25g of slurry projection.
[0178] (4) Half-cutting evaluation
[0179] 100 parts by mass of barium titanate (BaTiO3, manufactured by KCM Corporation), 7 parts by mass of polyvinyl butyral (manufactured by Sekisui Chemical Co., Ltd.), 3 parts by mass of dioctyl phthalate, and 3 parts by mass of a dispersant (DISPERBYK-103, manufactured by BYK-Chemie) are added to a mixed solvent of toluene:ethanol = 1:1 (volume ratio), and dispersed in a ball mill to prepare a slurry.
[0180] The slurry is uniformly coated on the release layer of the release film in a manner to have a thickness of 2 μm after drying, and then dried to form a ceramic green sheet. Using a rotary die cutter (RDC (FB) -A4, manufactured by Tsukaya Hatmono Co., Ltd.), the release film formed with the ceramic sheet is half-cut from the ceramic green sheet side in a manner to form a 16 mm × 32 mm square and a depth of about 3 μm from the surface of the release layer. The rotary die cutter blade uses a double-edged blade of 50°, a blade depth of 0.3 mm, and a blade height of 0.6 mm. The depth of the half-cut is adjusted by sandwiching a polyester film of appropriate thickness between the rotary die cutter blade and the ceramic green sheet and between the release film and the anvil roller. The cutting state of the cut portion is observed with an optical microscope (magnification of about 10 times) and evaluated in the following manner. It should be noted that photographs of each example corresponding to the case where the half-cutting property is evaluated as "○" to "×" are shown in Figure 1 to Figure 3 middle.
[0181] ○: No ceramic green sheet remains in the cut portion.
[0182] △: A very small amount of ceramic green sheet remains in the cut portion.
[0183] ×: A large amount of ceramic green sheet remains in the cut portion.
[0184] (5) Reusability evaluation
[0185] Regarding the recyclability, the size and number of foreign matter contained in the film were magnified 20 times by projection using a universal projector, and the number of foreign matter with a maximum diameter of 50 μm or more was counted. The measurement area was set to 0.05 m 2 .
[0186] ◎: The number of foreign objects is less than 10 / 0.05m 2 , there is no problem in using.
[0187] ○: Number of foreign objects is 10 / 0.05m 2 More than but less than 30 / 0.05m 2 , which slightly affects the flatness, but there is no problem in use.
[0188] △: The number of foreign objects is 30 / 0.05m 2 More than but less than 100 / 0.05m 2 , can be used for limited purposes.
[0189] ×: The number of foreign objects is 100 / 0.05m 2 As mentioned above, the deformation of the casting surface is very obvious and cannot be used.
[0190] (6) Number average molecular weight
[0191] The content was measured by gel permeation chromatography (GPC) and calculated as a polystyrene-equivalent value.
[0192] (7) Thickness of release layer
[0193] After cutting the release film into small triangular pieces, a Pt (platinum) layer with a thickness of 2nm is formed on the surface of the release layer by coating. The obtained sample is fixed in a multi-axis embedding capsule, embedded with epoxy resin, and sliced in a direction perpendicular to the surface direction of the film using a slicer ULTRACUT-S to obtain an ultra-thin sample with a thickness of 50nm. Next, the obtained ultra-thin sample is placed on a grid and steam-stained with 2% osmic acid at 60°C for 2 hours. Using the ultra-thin sample after steam staining, a transmission electron microscope LEM-2000 is used to observe the cross section of the film at an acceleration voltage of 100kV to measure the thickness of the release layer. The measurement is performed at any 10 points, and their average value is taken as the thickness of the release layer (unit: nm).
[0194] [Example 1]
[0195] The polyethylene terephthalate ([η]=0.64dl / g, Tg=78°C) containing 0.25% by mass of calcium carbonate particles with an average particle size of 0.6μm was melted by an extruder, passed through a filter with a filtration accuracy of 10μm, extruded from a die, and cooled by a cooling drum by a conventional method to form an unstretched film. Then, after being stretched to 3.3 times at 80°C in the longitudinal direction, the water-based coating liquid (aqueous coating composition) obtained in Manufacturing Example 1 was uniformly applied by a roll coater in such a manner that the product thickness became the release layer thickness shown in Table 2. It should be noted that the water-based coating liquid used was a coating liquid used within 24 hours after preparation.
[0196] Next, the coated film was dried at 105°C, stretched to 4.7 times in the transverse direction at 150°C, and then heat-set at 235°C for about 10 seconds to obtain a release film (thickness 25 μm) having a release layer formed by reacting and curing the water-based coating liquid, and the evaluation was performed. The evaluation results are shown in Table 2.
[0197] It should be noted that 40% by mass of the following raw materials are used: the release film parts that have not become products when collecting product rolls, and the release films that have not become products due to defects, are crushed according to each embodiment and comparative example until the major diameter of the film piece becomes less than about 5 mm, and then melted and regenerated to obtain the raw materials.
[0198] <Production Example 1>
[0199] (Sample 1A)
[0200] Using an emulsifier capable of stirring the entire container (manufactured by NPLabo Co., Ltd., device name "Super Planetary Stirrer"), a raw material containing 95% by mass of a1 of formula (1) with 100 mol%, b1 with 0 mol% and a number average molecular weight of 9000, and 5% by mass of polyoxyethylene tridecyl ether (manufactured by ADEKA CORPORATION, trade name "ADEKATOL TN-100") as a surfactant was mechanically emulsified in an aqueous medium to obtain an aqueous emulsion of sample 1A having a solid content of 40% by mass. In addition, the emulsion particle size was adjusted to an average particle size of 210 nm by adjusting the stirring speed and stirring time during emulsification.
[0201]
[0202] (Sample 2A)
[0203] Using an emulsifier capable of stirring the entire container (NPLabo Co., Ltd., device name "Super Planetary Stirrer"), a raw material containing 94% by mass of a2 of formula (2), 50% by mole, 50% by mole of b2, and a number average molecular weight of 4000 silicone oil, and 6% by mass of polyoxyethylene tridecyl ether (LION SPECIALTYCHEMICALS CO., LTD., trade name "LEOCOL TD-90") as a surfactant was mechanically emulsified in an aqueous medium to obtain a water dispersion of sample 2 having a solid content of 40% by mass. In addition, the emulsion particle size was adjusted to an average particle size of 170 nm by adjusting the stirring speed and stirring time during emulsification.
[0204]
[0205] (Water-based coating liquid)
[0206] As a water-based coating liquid, the solid content mass of the silicone of Sample 1A and Sample 2A was prepared to be the compounding amount shown in Table 2, and other components were set as shown below. The following coupling agent was mixed at 5 mass% relative to the total mass of the silicone, the following platinum-based catalyst was mixed at 50 ppm relative to the total mass of the solid content of Sample 1A and Sample 2A, and the following cross-linking reaction inhibitor was mixed at 100 ppm relative to the mass of the coating liquid, and the solid content concentration of the coating liquid was diluted with water to obtain the target release layer thickness to prepare the coating liquid.
[0207] · Coupling agent: 3-glycidoxypropyltriethoxysilane (manufactured by JNC Corporation, trade name "Sila-Ace S510")
[0208] Platinum-based catalyst: Platinum-based catalyst emulsion (manufactured by Wacker, trade name "CATALYST EM440"
[0209] Cross-linking reaction inhibitor: 1-ethynylcyclohexanol (manufactured by Alfa Lancaster)
[0210] [Example 2]
[0211] In Example 1, a release film was produced and evaluated under the same conditions as in Example 1 except that the sample 1B produced in Production Example 2 was used instead of the sample 1A to prepare the water-based coating liquid.
[0212] <Production Example 2> (Sample 1B)
[0213] Using an emulsifier capable of stirring the entire container (manufactured by NPLabo Co., Ltd., device name "Super Planetary Stirrer"), a raw material containing 95% by mass of a1 of formula (1) with 100 mol%, b1 with 0 mol% and a number average molecular weight of 5000, and 5% by mass of polyoxyethylene tridecyl ether (manufactured by ADEKA CORPORATION, trade name "ADEKA TOL TN-100") as a surfactant was mechanically emulsified in an aqueous medium to obtain an aqueous emulsion of sample 1B having a solid content of 40% by mass. In addition, the emulsion particle size was adjusted to an average particle size of 190 nm by adjusting the stirring speed and stirring time during emulsification.
[0214] [Example 3]
[0215] In Example 1, a release film was produced and the above evaluation was performed under the same conditions as in Example 1 except that Sample 1C produced in Production Example 3 was used instead of Sample 1A to prepare the water-based coating liquid.
[0216] <Production Example 3> (Sample 1C)
[0217] Using an emulsifier capable of stirring the entire container (manufactured by NPLabo Co., Ltd., device name "Super Planetary Stirrer"), a raw material containing 95% by mass of a1 of formula (1) with a value of 96 mol%, b1 with a value of 4 mol% and a number average molecular weight of 7000, and 5% by mass of polyoxyethylene tridecyl ether (manufactured by ADEKA CORPORATION, trade name "ADEKA TOL TN-100") as a surfactant was mechanically emulsified in an aqueous medium to obtain an aqueous emulsion of sample C having a solid content of 40% by mass. In addition, the emulsion particle size was adjusted to an average particle size of 200 nm by adjusting the stirring speed and stirring time during emulsification.
[0218] [Example 4]
[0219] In Example 1, a release film was produced and the above evaluation was performed under the same conditions as in Example 1 except that Sample 1D produced in Production Example 4 was used instead of Sample 1A to prepare the water-based coating liquid.
[0220] <Production Example 4> (Sample 1D)
[0221] Using an emulsifier capable of stirring the entire container (NPLabo Co., Ltd., device name "super planetary stirrer"), a raw material containing 95% by mass of formula (A) 2 mol%, formula (B) 4 mol%, formula (C) 90 mol%, formula (D) 2 mol%, formula (E) 2 mol% and a number average molecular weight of 8000 silicone oil, and 5% by mass of polyoxyethylene tridecyl ether as a surfactant (ADEKA CORPORATION, trade name "ADEKA TOL TN-100") was mechanically emulsified in an aqueous medium to obtain a water-based emulsion of sample 1D having a solid content of 45% by mass. In addition, the emulsion particle size was adjusted to an average particle size of 200 nm by adjusting the stirring speed and stirring time during emulsification.
[0222]
[0223] [Example 5]
[0224] In Example 4, except that the contents of Sample 1D and Sample 2A were changed as shown in Table 2 when preparing the water-based coating liquid, release films were produced and evaluated as described above under the same conditions as in Example 4. The results are shown in Table 2.
[0225] [Comparative Examples 1-2]
[0226] In Examples 4 and 5, release films were prepared and evaluated under the same conditions as in Examples 4 and 5 except that the water-based coating liquid obtained in Production Example 5 was used instead of the water-based coating liquid obtained in Production Example 4. The results are shown in Table 2.
[0227] <Production Example 5>
[0228] (Sample 1E)
[0229] Using an emulsifier capable of stirring the entire container (manufactured by NPLabo Co., Ltd., device name "Super Planetary Stirrer"), a raw material containing 96% by mass of a1 of formula (1), 97% by mole, 3% by mole of b1, and a number average molecular weight of 30,000 silicone oil, and 4% by mass of polyoxyethylene tridecyl ether (manufactured by Lion Specialty Chemicals Co., Ltd., trade name "LEOCOL TD-90") as a surfactant was mechanically emulsified in an aqueous medium to obtain an aqueous emulsion of sample 1E having a solid content of 50% by mass. In addition, the emulsion particle size was adjusted to an average particle size of 200 nm by adjusting the stirring speed and stirring time during emulsification.
[0230] (Sample 2B)
[0231] Using an emulsifier capable of stirring the entire container (NPLabo Co., Ltd., device name "Super Planetary Stirrer"), a raw material containing 94% by mass of a3 of formula (2), 50% by mole, 50% by mole of b3, and a number average molecular weight of 8000 silicone oil, and 6% by mass of polyoxyethylene tridecyl ether (LION SPECIALTYCHEMICALS CO., LTD., trade name "LEOCOL TD-90") as a surfactant was mechanically emulsified in an aqueous medium to obtain a water dispersion of sample 2 having a solid content of 50% by mass. In addition, the emulsion particle size was adjusted to an average particle size of 180 nm by adjusting the stirring speed and stirring time during emulsification.
[0232] (Water-based coating liquid)
[0233] Aqueous coating liquids were prepared under the same conditions as in Production Example 1 except that the solid content mass of silicone in Sample 1E and Sample 2B was adjusted to the blending amount shown in Table 2.
[0234] [Table 2]
[0235]
[0236] As shown in Table 2, in Examples 1 to 5, since the erosion rate is 0.003 μm / g or more, the half-cutting property evaluation is good, and when the sheet-like molded product is peeled off after half-cutting, problems due to adhesion to the half-cut portion are less likely to occur. In contrast, in Comparative Examples 1 and 2, the erosion rate is less than 0.003 μm / g, and although the surface free energy is low, the half-cutting property evaluation is low, and when the sheet-like molded product is peeled off after half-cutting, problems due to adhesion to the half-cut portion are more likely to occur.
[0237] In addition, in Examples 1 to 5, the surface free energy was an appropriate value, and the coating uniformity and recycling property were also good.
[0238] Industrial Applicability
[0239] The release film of the present invention is less likely to cause problems due to adhesion to the half-cut portion when peeling off the sheet-like molded product after half-cutting. Therefore, the release film of the present invention can be easily used as a material in various processes and is also recyclable, and has extremely high industrial utilization value.
Claims
1. A release film comprising a substrate film and a release layer, The erosion rate of the release layer is 0.003 μm / g or more, and the erosion rate is the average particle size (D 50 ) is the erosion rate of a slurry formed by dispersing 0.3 μm polygonal alumina particles in water.
2. The release film according to claim 1, wherein The release layer is formed by reacting and solidifying a reaction-curable composition containing an organosilicon-based compound.
3. The release film according to claim 2, wherein The reaction-curable composition comprises an alkenyl-containing organosilicon having a SiO 4 / 2 Represents the Q unit.
4. The release film according to claim 1, wherein The substrate film is a polyester film.
5. The release film according to any one of claims 1 to 4, wherein The release film is a release film for a laminated ceramic capacitor or a release film for a resin sheet.
Citation Information
Patent Citations
Polysiloxane coating material and releasing film
JP2003292894A
Polysiloxane composition and releasing film
JP2003292895A
Mold release film for molding green sheet for multilayer ceramic capacitor
JP2012006213A
Silicone release polyester film
JP2021011081A
Release film for producing ceramic green sheet
WO2019065214A1